Spray coverage and pest management efficacy of a solid set canopy delivery system in high density apples - Owen‐Smith, Paul (Wiley, 2019)
BACKGROUND: Air blast sprayers are not optimized for spraying the short statured trees in modern apple orchards, resulting in off target drift and variable coverage. A solid set canopy delivery system (SSCDS) consisting of a microsprayer array distributed throughout the orchard was investigated as a replacement agrochemical application method in this study. SSCDS's have the potential to optimize coverage, rapidly spray applications, and remove the operator and tractor from the orchard. RESULTS: Air blast and SSCDS applications were compared using water sensitive paper, bioassays, and pest damage assessments. Pest management and coverage were compared using application volumes of 700 and 795 L ha−1, respectively. In 2013, adaxial coverage measurements showed no difference between the treatments, but air blast sprayers had higher coverage levels on the abaxial surfaces. There were no significant differences in coverage in 2014. Bioassays using Choristoneura rosaceana fed on leaf discs treated by the SSCDS displayed 95.8% mortality in 2013 and 94.2% mortality in 2014, and air blast treated larval mortality was 95% in 2013 and 100% in 2014. Damage evaluations in both years generally showed no significant differences between the air blast plots and the SSCDS plots, but significant differences between the treated plots and untreated control. CONCLUSIONS: The prototype SSCDS was an effective pest management tool in high density apples, and offered a number of advantages over an air blast. Further engineering and research into coverage optimization would offer producers a novel tool for foliar agrochemical applications. © 2019 Society of Chemical Industry. © 2019 Society of Chemical Industry